Experience with ConsultWiz – The Simultaneous Electronic Notification, Documentation, and Tracking of Inpatient Consult Requests - Weinberg, Stuart T. (American Medical Informatics Association, 2006)
ConsultWiz is a component of Vanderbilt's electronic order-entry system that facilitates and documents requests for medical and surgical consult services in the adult and children's hospitals. Piloted in the Dept of Medicine in Spring, 2005, ConsultWiz was expanded to include all remaining adult services in July, 2005 and all pediatric consult services in October, 2005. By February, 2006, over 10,000 consult requests were placed. Details and issues in the development and implementation of ConsultWiz are discussed.